PARENTAL SMOKING HABITS AND THE INCIDENCE OF ACUTE RESPIRATORY TRACT INFECTIONS IN TODDLERS - Putri, Nesa Ayu Murthisari; Desmawati, Elis (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Acute Respiratory Tract Infection (ARI) remains a major cause of morbidity and mortality in toddlers in developing countries, including Indonesia. Toddlers are particularly vulnerable to ARI because their immune systems and respiratory tracts are not yet fully developed. One significant yet often overlooked environmental factor is parental smoking at home. Based on these conditions, this study was conducted to determine the relationship between parental smoking habits and the incidence of ARI in toddlers. This research is a quantitative analytical study with a cross-sectional approach involving 30 parents with toddlers in RT 03 RW 02, Sukaraya Village, within the working area of the Sukaraya Community Health Center (UPTD). A total sampling technique was used to obtain a comprehensive sample. Data were collected through interviews using a structured checklist instrument, then analyzed using the Chi-Square test. The results of the analysis showed that of the 17 parents who smoked, 47.1% of toddlers experienced ARI. In contrast, of the 13 parents who did not smoke, only 7.7% of toddlers experienced ARI. Statistical testing showed a p-value of 0.042 (p<0.05), indicating a significant association between parental smoking habits and the incidence of ARI in toddlers. This finding underscores the importance of family health education and interventions, particularly in reducing exposure to cigarette smoke at home, as an effort to prevent ARI and continuously protect toddler health.